MUATAN SOSIAL-BUDAYA DALAM BUKU TEKS PELAJARAN BAHASA ASING - Herudjati Purwoko (Master Program in Linguistics, Diponegoro University, 2010)
This article is on the social and cultural contents of textbooks for foreign language learners. Some textbooks, published for foreign learners in various languages, are selected in random way before being observed carefully. The basic assumption is that most (or even all) textbooks will introduce to the prospective learners some socio-cultural information embedded in the target language which, inevitably, the learners will have to deal with. The sociolinguistics has it that no language can be separated from the socio-cultural issues. The fact enables any language to survive and linger on. Therefore, all good textbooks must contain the socio-cultural issues relevant to the current language usage in daily interactions